2003
DOI: 10.1128/jb.185.2.645-653.2003
|View full text |Cite
|
Sign up to set email alerts
|

Development of Methicillin Resistance in Clinical Isolates of Staphylococcus sciuri by Transcriptional Activation of the mecA Homologue Native to the Species

Abstract: The ␤-lactam resistance gene mecA was acquired by Staphylococcus aureus from an extraspecies source. The search for the possible origin of this gene has led to the identification of a close structural homologue of mecA as a native gene in the animal species Staphylococcus sciuri. Surprisingly, the overwhelming majority of S. sciuri isolates were fully susceptible to ␤-lactam antibiotics in spite of the ubiquitous presence of the mecA homologue in the bacteria. We now describe two unusual S. sciuri strains isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 27 publications
3
66
0
Order By: Relevance
“…Alterations to the promoter region of mecA1 are necessary for high-level mecA1 expression and oxacillin resistance in Staph. sciuri (Wu et al, 2001(Wu et al, , 2005Couto et al, 2003). In our study, none of the Staph.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Alterations to the promoter region of mecA1 are necessary for high-level mecA1 expression and oxacillin resistance in Staph. sciuri (Wu et al, 2001(Wu et al, , 2005Couto et al, 2003). In our study, none of the Staph.…”
Section: Discussionmentioning
confidence: 81%
“…sciuri isolates are susceptible to β-lactam antimicrobials. However, alterations in the promoter regions of mecA1 upregulate mecA1 expression and confer methicillin resistance (Wu et al, 2001(Wu et al, , 2005Couto et al, 2003). Methicillin-resistant staphylococci are often also resistant to other classes of drugs such as aminoglycosides and macrolides (Woodford 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Couto et al (55) identified a mecA gene in a methicillin-sensitive Staphylococcus sciuri with 88% homology on the amino acid level to MRSA. Transduction of the S. sciuri mecA into an MSSA resulted in increased resistance to methicillin coupled with the detection of PBP2a (56). These studies therefore suggest one possible source of the mecA element in S. aureus.…”
Section: Methicillin Resistancementioning
confidence: 83%
“…aureus (MSSA) homologue exists (Archer and Neimeyer, 1994) it has been suggested that it was transferred horizontally from a coagulase-negative staphylococcus (CoNS) such as S. sciuri (Couto et al, 1996;Couto et al, 2003). The conjugative transposon containing tetM (tetracycline resistance) has been suggested to pass between Clostridia and staphylococci (Ito et al, 2003), and empirical support for the movement of mobile elements between staphylococci and other low GC gram negative bacteria (Gill et al, 2005), and the potential transfer of vanA (vancomycin resistance) from Enterococcus faecalis to S. aureus (Weigel et al, 2003) lends weight to the possibility of a common gene pool available to many bacterial species (Hanssen et al, 2004).…”
Section: Mrsa In the Non-clinical Environment A Methicillin Resismentioning
confidence: 99%